Consumer responses to a future UK food system. Issue 2 (1st February 2016) - O'Keefe, Laura; McLachlan, Carly; Gough, Clair; Mander, Sarah; Bows-Larkin, Alice
Abstract : Purpose: – The purpose of this paper is to describe research exploring consumer responses to potential changes in food-related practices to mitigate and adapt to climate change. Design/methodology/approach: – Six focus groups explored consumer responses to measures to intended to mitigate the emissions from, and adapt to the impacts of climate change. These included: meat reduction, greater reliance on seasonal British food, meal replacement tablets, laboratory grown meat, communal eating houses, genetically modified food and food waste. Practice theory provided the lens to interpret the changes to meanings, competences and materials associated with food consumption. Findings: – Changes that could be assimilated within existing competencies were viewed more positively, with lack of competence a key barrier to accommodating change. At present, climate change and sustainability do not influence purchasing decisions. Policy measures delivering multiple benefits ("win-wins"), of which environmental performance may be one, stand an improved chance of establishing more sustainable practices than those focusing exclusively on environmental drivers. Originality/value: – Awareness of the role of sustainable food systems in the context of anthropogenic climate change is growing. Whilst scientific and technological research explores methods for reducing emissions and building resilience in food supply chains to changes in climate, there is comparatively little study of how consumers perceive these proposed "solutions". This research provides a comprehensive overview of consumer responses to potential changes in eating practices related to climate change mitigation and adaptation and is of value to policy makers, academics and practitioners across the food supply chain.